Desafios da Pesquisa Participativa e Restituição em Projeto de Pesquisa junto a Pequenos Agricultores. - João Roberto Correia; Patricia Goulart Bustamante; Laure Emperaire; Danielle Mitja (Cahiers des Amériques Latines)
The use of natural resources is a challenge for rural communities in the Cerrado biome. This paper discusses the research and its participatory restitution forms from the information obtained with the farming communities in Rio Pardo de Minas, state of Minas Gerais, Brazil. The project was developed with different agriculture science methodologies, including approaches of the humanities and social sciences. The point of convergence was the direct involvement with the farmers. The information returning occurred in different aspects like the discussion of results with the rural families and during the local and regional planning for natural resources use and agricultures activities for the future stages. The information restitutions, followed by their analysis and lately returned to the local and regional communities, will improve the technologies and processes established nowadays.